(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
In this paper are presented an empirical analysis of co-integration interest rates inPoland. The models are estimated whit the Johansen co-integration methodology. The data used is dailyinterest rates in the period 02.01.2003-22.07.2008. The findings re-veals a co-integration relation. There is long-run relationship between interest rates inPoland.